Flaxseed gum-biopolymers interactions driving rheological behaviour of oropharyngeal dysphagia-oriented products - Vieira, J. (2021)
Viscosity-modified diet through thickeners is used as a strategy to circumvent swallowing problems by oropharyngeal dysphagia patients. Most commercial products present xanthan and starch in their formulations, but flaxseed gum (FG) is a potential thickener for liquid food that provides additional health benefits. FG was mixed either with modified starch (MS) and/or xanthan gum (XG), varying biopolymersâ concentration according to a central composite rotational design in which rheological and colour properties in water were the evaluated responses. All formulations showed a shear time-independent and shear-thinning behaviour, mainly influenced by XG and MS concentrations. In oscillatory measurements, the formulations presented a prevailing elastic character attributed to MS and mainly to XG, which despite the lower concentration in which it was incorporated, exerted a similar influence on this rheological property. However, the increase of FG concentration was the most significant factor influencing viscosity, but also favoured an increase of both viscoelastic moduli mainly G'. Analysis of the microstructure disclosed different network structures as a result of biopolymers interactions, which was related to rheological behaviour giving insights to design new thickeners for dysphagia management. In addition, the amount of glucose released after in vitro digestion was evaluated and compared to a commercial MS-based thickener. Interestingly, the commercial formulation showed a glucose release significantly higher than the proposed FG/MS/XG-based formulations. These results open the opportunity to tailor the rheological characteristics of food systems by adding and combining natural ingredients, improving technological and nutritional properties.